Efficient Polarization-Insensitive All-Fiber Wavelength Conversion in C-Band Using Feedback in Highly Non-Linear Fibers - Anadi Agnihotri; Arunabh Deka; Pradeep Kumar Krishnamurthy (IEEE Photonics Journal)
We propose and experimentally demonstrate a novel dual-pump feedback-based polarization-insensitive wavelength conversion technique using four-wave mixing (FWM) in highly nonlinear fiber (HNLF). By feeding the residual pumps at the output of the HNLF back to the fiber in orthogonal polarization state with respect to the original forward path pumps, we achieve approximately 6 dB improvement in FWM conversion efficiency with negligible polarization sensitivity. A simple theoretical treatment of polarization independent operation is presented. The experimental results closely match the theory and simulation results. Comprehensive comparisons with co-polarized dual pumps, orthogonal pumps, and single pump schemes highlight the significant reduction in polarization sensitivity from over 8 dB in the single pump scheme to approximately 0.7 dB, by the proposed scheme. As an application to the proposed technique, we experimentally demonstrate successful wavelength conversion of 10 and 20 Gbps 4-PAM format signals from 1552.58 nm to 1554.28 nm.